Tradition Amidst Modernization: The Rise and Fall of the Tradition of Pesta Tebu in Cirebon District, West Java - Meliani, Wini; Iqbal, Asep Muhamad (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article examines tradition amidst modernization focusing on the rise and fall of the Pesta Tebu tradition and its relationship with the technological advancement of sugar factories in Cirebon district, West Java. Two villages were selected for this study as they represent sites where the Pesta Tebu tradition experienced the rise and fall in the face of modernization. This article uses a comparative method with a qualitative approach and the techniques of non-participant observation and interviews for data collection. Employing the narrative method as a data analysis technique, this study argues that modernization in the form of industrialization of sugar production resulted in the rise and fall of the Pesta Tebu tradition. When the management of the sugar factories renewed the technology of sugar production, the Pesta Tebu tradition survived and continued, but when this was not the case, the Pesta Tebu tradition died out. All this shows that modernization did not destroy tradition, but rather contributed to the rise and survival of tradition within communities. Comparing two cases of the Pesta Tebu tradition, this article contributes to a better understanding of the impact of modernization on tradition in that industrialisation resulted in a varied impact on tradition.